Selected Topics in Neonatal Care - Mauricio Barría, R. (IntechOpen, 2018)
Neonatology is one of the areas of greatest development and evolution within pediatrics. The technoscientific advances in this area have led to an increase in the survival of premature infants who sometimes require sophisticated care. However, there is essential care that must be included in all centers that care for high-risk babies. This book includes important topics related to neonatal care grouped into four sections. In 14 chapters that address relevant issues about neonatal care, the book seeks to contribute to the clinical work of the health teams of neonatal units. Specialists in the field of neonatology from different countries have developed these chapters and through them they hope to share part of their experience.